2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944943
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor cortex reorganization in subacute and chronic stroke: A neuronavigated TMS study

Abstract: The integrity of the corticospinal system is an important biomarker for recovery from stroke. However, mapping the topography of the corticospinal system in subacute stroke is not trivial and how it changes over the course of recovery is poorly understood. We intend to use a transcranial magnetic stimulation (TMS) based mapping approach to quantify the topographic landscape of corticospinal activation in the ipsi- and contralesional sensorimotor cortices in the subacute and chronic phase of stroke. Mapping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In particular, it has been shown that an intact position sense following stroke strongly correlates with the likelihood of motor recovery of the hemiplegic arm (Kusoffsky et al, 1982 ; Smith et al, 1983 ; Rand et al, 1999 ; Schabrun and Hillier, 2009 ). This is further supported by the recent neurophysiological finding that sensory input is integral in the preservation of cortical representation in both motor and sensory areas (Schabrun and Hillier, 2009 ; Chieffo et al, 2013 ; Yarossi et al, 2014 ). Indeed, the absence or reduction of sensory input in stroke subjects is known to bring about learned non-use and impaired or lost ability to react to or process sensory stimuli in the space contralateral to the brain lesion, a condition referred to as unilateral spatial neglect (Taub and Berman, 1963 ; Kerkhoff and Rossetti, 2006 ).…”
Section: Introductionmentioning
confidence: 59%
“…In particular, it has been shown that an intact position sense following stroke strongly correlates with the likelihood of motor recovery of the hemiplegic arm (Kusoffsky et al, 1982 ; Smith et al, 1983 ; Rand et al, 1999 ; Schabrun and Hillier, 2009 ). This is further supported by the recent neurophysiological finding that sensory input is integral in the preservation of cortical representation in both motor and sensory areas (Schabrun and Hillier, 2009 ; Chieffo et al, 2013 ; Yarossi et al, 2014 ). Indeed, the absence or reduction of sensory input in stroke subjects is known to bring about learned non-use and impaired or lost ability to react to or process sensory stimuli in the space contralateral to the brain lesion, a condition referred to as unilateral spatial neglect (Taub and Berman, 1963 ; Kerkhoff and Rossetti, 2006 ).…”
Section: Introductionmentioning
confidence: 59%
“…In addition to NMSE, we computed several common map features as outcome measures: map volume, map area, and center of gravity in both the rostral-caudal plane (denoted COGx1) and in the medial-lateral plane (COGx2). Map volume and map area were calculated using double trapezoidal integration of the interpolated maps [44]. COGx1 and COGx2 were computed using standard equations [42].…”
Section: Assessment Of Accuracy Of the Sampling Methodsmentioning
confidence: 99%
“…MEP amplitudes and stimulation points were interpolated to a 7 × 7 cm mesh of 0.375 mm resolution (centered on the M1 hotspot) using cubic surface interpolation [52, 53] allowing comparisons across maps and sessions. Extent of the representation producing corticospinal output (MEPs) for individual muscles, or map area, was calculated using double trapezoidal integration of the interpolated map [43].…”
Section: Methodsmentioning
confidence: 99%